A Biotemplating Route for the Synthesis of Hierarchical Fe2O3 with Highly Dispersed Carbon as Electron‐Transfer Channel. Issue 1 (30th January 2020) - Yang, Zhao; Kang, Jianxin; Li, Lidong; Guo, Lin
Abstract: Although the preparation of carbon composites has made great progress, the construction of systems comprising uniformly dispersed carbon as a framework to link active constituents still remains a challenge. Herein, a hierarchical Fe2 O3 /C composite was synthesized in a one‐step biotemplating route, where agarose was firstly reacted with Fe 3+ and Ca 2+ ions, which resulted in a competitive interaction between these ions and the hydroxy groups, then partly calcined to achieve the final product that consisted of α‐Fe2 O3 nanoparticles embedded in highly dispersed carbon. The carbon within the composite acts as an efficient photoelectron transfer channel to improve conductivity during photocatalysis. The hierarchical Fe2 O3 /C composite exhibited a photodegradation rate constant (k) of 0.091 min −1, more than four times that of α‐Fe2 O3 (0.020 min −1 ). Abstract : Inspired by Nature : An Fe2 O3 /C nanocomposite was synthesized in a biotemplating route. Its spindle‐shaped nanostructure was characterized by spherical‐corrected transmission electron microscopy. The highly dispersed carbon acts as an electron‐transfer channel to improve photocatalytic activity.